The Relationship Between Verbal Ability and Critical Thinking Skill: The Implementation of Susan Loucks Horsley Model - Wulandari, Ana Yuniasti Retno; Nurhayati, Nurhayati (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2018)
Susan Loucks Horsley is a learning model that can connect science and technology. This model can help students adapt to the increasingly changing scientific and technology of the 21st century. Students are challenged with issues that require the use of scientific information, technology, verbal ability, critical thinking, and conceptual understanding in making decisions. It is because verbal ability and critical thinking are needed in solving problems hence this research aims to know the correlation of verbal ability with students' critical thinking skill in science learning of vibration, wave and sound material using Susan Loucks Horsley model. The sample of this research is the students of VIII A SMP N 1 Pamekasan. The collecting data technique use tests to measure the students' verbal ability and critical thinking skills. The data analysis uses Pearson correlation. The result of this research shows there is a correlation between verbal ability with students' critical thinking skill in science learning of vibration, wave and sound material using Susan Loucks Horsley model with the value of Pearson correlation coefficient 0,656 and significance 0.000. This research has an implication that the teachers should be appropriate in applying the learning model that can grow the students’ verbal ability and critical thinking skill.